Detection of Gene Promoter Methylation and Protein Expression of p21 in Psoriasis - Xin-Mei Liu; Dong Luo; Hui-Qin Wang; Jing-Zhan Zhang; Xiao-Jing Kang; Wei-Dong Wu (Wolters Kluwer Health, 2019)
Abstract. Object:. The study was aimed to detect the methylation patterns in psoriasis tissues. Methods:. We collected 15 psoriasis tissues and 19 uninvolved psoriatic samples from psoriasis patients, and 3 normal skin samples from healthy control, and investigated the methylation levels of p21 gene promoter by pyrosequencing analysis. The expression of p21 protein was detected by immunohischemistry in 38 psoriatic tissues and 16 uninvolved samples from psoriasis patients, and 3 normal samples from healthy control. The differences among the three groups were analyzed by Chi-square test. Results:. We found that there was no significant difference in the frequency of p21 gene promoter methylation among the three groups (P=0.204), howerver the p21 protein expression were different among the three groups (P=0.007). Conclusion:. This methylation marker maybe not an indicator for the detection and monitoring of psoriasis.